Impact of transformational leadership on the person-organization fit of Chinese nurses: The moderating effect of emotional intelligence - Nan Liu; Lin Wang; Jiemei Yin (Wiley, 2023)
Abstract Aims To explore the relationships between transformational leadership and person-organization fit, as well as to test the moderating effects of emotional intelligence. Design A descriptive cross‐sectional study design was used to conduct an online questionnaire survey among 326 nurses in Chinese hospitals between March and June 2022. Methods Transformational leadership, person-organization fit and emotional intelligence were measured using the Person-Organization Fit Scale, Transformational Leadership Questionnaire and Emotional Intelligence Scale. Hierarchical multiple linear regression models and simple slope analyses were used. Results Transformational leadership had a significant positive impact on person-organization fit. Furthermore, emotional intelligence had a conditional moderating effect on the relationship between transformational leadership and nurses' person-organization fit. Under a high level of emotional intelligence, transformational leadership had a stronger positive effect on person-organization fit, while under a low level of emotional intelligence, the relationship between the two was not significant. Conclusion Transformational leadership has a positive predictive effect on person-organization fit, but this positive predictive effect is driven by conditional effect. The emotional intelligence of nurses plays a moderating role between them.